Physiological correlates to off-road cycling performance - Impellizzeri, F. M.; Rampinini, E.; Sassi, A.; Mognoni, P.; Marcora, S. (Journal of Sports Sciences, 2005)
The aim of this study was to examine the relationships between maximal and submaximal tests for aerobic fitness and performance in an off-road cross-country circuit race. Thirteen competitive off-road male cyclists participated in the study. Peak oxygen uptake (VO2peak), peak power output, and lactate thresholds corresponding to 1 mmol·l1 above baseline (lactate threshold) and to 4 mmol·l1 (onset of blood lactate accumulation) were measured during an incremental cycling test. Race time and final ranking within the same group of cyclists were determined during a cross-country off-road competition. All correlations between the measured parameters of aerobic fitness and off-road cycling performance were significant, particularly between race time and physiological parameters scaled to body mass 0.79 (r=0.68 to 0.94; P<0.05) and between final ranking and physiological parameters expressed relative to body mass0.79 (r=0.81 to 0.96; P<0.001). Moreover, there was a large difference (effect sizes=1.12-1.70) in all measured parameters of aerobic fitness between the group of six cyclists with a race time above the median and the group of six cyclists with a race time below the median (P<0.05). In conclusion, the results of this study provide empirical support to the widespread use of these maximal (VO2peak, peak power output) and submaximal (lactate thresholds) parameters of aerobic fitness in the physiological assessments of off-road cyclists. Furthermore, our results suggest body size should be taken into account when evaluating such athletes.